Perlindungan Hukum Pengemudi Ojek Online Atas Kontrak Perjanjian Perusahaan Gojek (Study Kasus Pasca Putusan Mahkamah Konstitusi No. 41/PUU-XVI/2018) (Jurnal Sosial Humaniora dan Pendidikan, 2022)
The current era of modernization means that all humans have to keep up with changing times which are increasingly rapid and sophisticated. For this reason, equipment was created that can facilitate and lighten the burden of our daily tasks. The approach method used is the normative juridical and empirical juridical approaches. The decision of the Constitutional Court is a decision that is final and binding and immediately has permanent legal force starting from the time it is pronounced in a plenary session open to the public and is erga omnes (applies to everyone) which must be obeyed and must be implemented directly (self executing). Conclusion 1. Legal protection for online motorcycle taxi drivers following the Constitutional Court decision Number 41/PUU-XVI/2018 is a constitutional recognition of economic rights and the right to obtain decent work for every individual who acts as a human rights subject, and is guaranteed in the Regulation of the Minister of Transportation of the Republic of Indonesia Number 12 of 2019 2. Online motorcycle taxis do not include passenger vehicles